2020
DOI: 10.1007/s10439-020-02603-z
|View full text |Cite
|
Sign up to set email alerts
|

A Combined In Vivo, In Vitro, In Silico Approach for Patient-Specific Haemodynamic Studies of Aortic Dissection

Abstract: The optimal treatment of Type-B aortic dissection (AD) is still a subject of debate, with up to 50% of the cases developing late-term complications requiring invasive intervention. A better understanding of the patient-specific haemodynamic features of AD can provide useful insights on disease progression and support clinical management. In this work, a novel in vitro and in silico framework to perform personalised studies of AD, informed by non-invasive clinical data, is presented. A Type-B AD was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…Similar oscillations were observed in a 0D model reported by Reference [24]. Usually, the oscillations are filtered out in experimental results 25 . Our study shows that this oscillation may not be merely an artifact; especially if the oscillation of the wall is significant.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar oscillations were observed in a 0D model reported by Reference [24]. Usually, the oscillations are filtered out in experimental results 25 . Our study shows that this oscillation may not be merely an artifact; especially if the oscillation of the wall is significant.…”
Section: Discussionsupporting
confidence: 87%
“…Usually, the oscillations are filtered out in experimental results. 25 Our study shows that this oscillation may not be merely an artifact; especially if the oscillation of the wall is significant. Comparing the results in Figure 5 shows that the boundary condition has a significant effect on the fluctuation of the pressure and the flow rates.…”
Section: Discussionmentioning
confidence: 56%
“…Pirola et al ( 18 ) also compared their computational analysis with four-dimensional (4D) MRI. Bonfanti et al ( 19 ) conducted pulsatile in silico and in vitro analysis on the patient-specific Type B aortic dissection models. At present, no fluid-structure interaction (FSI) studies have been published on aortic dissections ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have reported the importance of personalised computational fluid dynamics (CFD) methods along with imaging techniques to develop diagnosis and controlling approaches of aortic disease, in order to customize patient-specific treatment outcomes 23 29 . Some studies have shown the importance of the combination of particle image velocimetry and CFD simulations in type-B AD in pre-procedural planning, clinical decision support, and CFD models validation 30 , 31 . Several studies have focused on TEVAR based on the prediction of thrombus formation and growth of the FL 13 , 32 35 .…”
Section: Introductionmentioning
confidence: 99%